2015
DOI: 10.18632/oncotarget.3309
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Desmoglein 2 and Patched 1 accelerates chemical-induced skin tumorigenesis

Abstract: Aberrant activation of Hedgehog (Hh) signaling is causative of BCCs and has been associated with a fraction of SCCs. Desmoglein 2 (Dsg2) is an adhesion protein that is upregulated in many cancers and overexpression of Dsg2 in the epidermis renders mice more susceptible to squamous-derived neoplasia. Here we examined a potential crosstalk between Dsg2 and Hh signaling in skin tumorigenesis. Our findings show that Dsg2 modulates Gli1 expression, in vitro and in vivo. Ectopic expression of Dsg2 on Ptc1+/lacZ back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Our work and that of others has demonstrated that Dsg2 in particular can enhance key mitogenic signaling cascades both within individual cancer cells and in adjacent ones (14, 15, 25). Localized expansion, invasion, and microenvironment manipulation by malignant clones is particularly important for the progression of HNSCC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our work and that of others has demonstrated that Dsg2 in particular can enhance key mitogenic signaling cascades both within individual cancer cells and in adjacent ones (14, 15, 25). Localized expansion, invasion, and microenvironment manipulation by malignant clones is particularly important for the progression of HNSCC.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, Dsg2 activates multiple growth and survival signaling pathways when overexpressed in transgenic mice and SCC cells (12, 15). Interestingly, we observed hedgehog activity in the underlying dermis of the tumors suggesting a paracrine mechanism of activation by Dsg2 (14). Here, we explore EV as a signaling conduit and illustrate that Dsg2 is present in EVs as a processed fragment and that overexpression of Dsg2 in keratinocytes alters the number and protein content of EVs.…”
mentioning
confidence: 90%
“…Interestingly, these signaling pathways are downstream of the epidermal growth factor receptor (EGFR) and activation with EGF increases association of EGFR binding to Dsg2 [20]. Furthermore, Dsg2 upregulates Hedgehog signaling and in response to chemical carcinogens, enhances BCC and SCC tumor development [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Hh signaling was found to override p53-mediated tumor suppression in BCCs, thus acting as a positive feedback loop in promoting oncogenesis (117, 118). In fact, in humans, high frequency and co-existence of genetic alterations in both PTCH and p53 genes have been identified in BCCs from both normal population and atomic bomb survivors (119, 122). PARP-1 is another important protein found to cooperate with Ptch in the suppression of BCCs induced by radiation exposure (120).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Brennan-Crispi et al . showed that Desmoglein 2 (Dsg 2) may synergize with Hh signaling to promote chemical-induced BCC development (122). However, the role of Dsg 2 in pathogenesis of Radiation-induced BCCs remains unclear at this time.…”
Section: Introductionmentioning
confidence: 99%